Couple Conflict and Music Utilisation. (2020) - Smith, Kevin M.; Martin, Gina
Abstract: It is believed that conflict exists on a spectrum, which holds interest for many relationship researchers. However, it is not well understood how music is utilised within couples when they engage in conflict, considering music has been known to assist in reducing physiological, emotional, and social regulation. The proposed study explored how music was utilised in times of conflict for couples through a grounded theory approach. The main themes that emerged were: variability of choice, knowledge of partner's habits, communication, similarity of style, relational distance, repair attempt, music utilisation as relational engagement, emotional regulation, and hopeful togetherness. These themes are presented in a theoretical model of how couples utilise music to regulate social, emotional, and biological domains of their relationship.